A silver-catalyzed modular intermolecular access to 6,6-spiroketals - Ahrens, Alexander; Heinrich, Niklas; Kohl, Simon; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2019)
A modular synthesis of 6,6-spiroketals via silver catalysis is reported. By combining an intermolecular Michael addition and a 6-endo-dig cyclization, this cascade reaction allows the modular preparation of highly substituted 6,6-spiroketals by combining two substrate molecules. Established methods accessing this interesting substructure are complemented by this new transformation. The protocol tolerates diverse substitution patterns and functional groups.